Algebra: A Combined Approach (4th Edition)

Published by Pearson
ISBN 10: 0321726391
ISBN 13: 978-0-32172-639-1

Chapter 8 - Section 8.2 - Introduction to Functions - Practice: 17

Answer

$f$($x$) = $3x^{2}$ - $x$ + 2 when $f$(-1) $f$(-1)= 6

Work Step by Step

$f$($x$) = $3x^{2}$ - $x$ + 2 when $f$(-1) First replace $x$ with -1 $f$(-1) = $(3 \times-1)^{2}$ - (-1) + 2 Next multiply 3 and -1 (which makes 3 negative) and add 1 and 2 (When a negative is subtracted it becomes positive) $f$(-1) = $-3^{2}$ - 3 $f$(-1) = 9 - 3 $f$(-1) = 6
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.